(untitled) (Aristonothos. Rivista di Studi sul Mediterraneo Antico, 2012)
A little note (Pollux 4, 91) concerning the Olympian and Delphian victories of an Hyblean keryx, Archias, in the IV a.C., enables us to consider some characteristics and developments of the heralds competition in the panhellenic Games from the classical times onward. Likewise, the patronymic of Archias, Eukles, lends itself to some remarks upon the hereditary transfer of this profession, as suggested by Pollux himself and by a series of inscriptions from the Athenian agorà (from IV to II a.C.). Moreover, it is preferable, for chronological reasons, to connect the ethnic of the herald with one of the indigenous Hyblai, and not with the Megarian colony. The close connections between the Greek settlements and the indigenous centres in Sicily is however demonstrated by several exchanges and crowded relationships in the onomastic field, and can be explained with the Dionysios I annexation’s strategy towards the Siculian towns of the south-east area of Sicily.